Kulturoznawcze badanie intertekstualnych gier z kanonem. Propozycje teoretyczno-metodologiczne - Jankowska, Małgorzata (Humaniora. Czasopismo Internetowe, 2021)
The role the canon plays in culture will be discussed in the paper. The canon can be seen as one of the most important media of cultural memory, a kind of cultural grammar or a vital semantic resource which influences a huge amount of new texts. This sort of textual variations on the canon may be considered secondary cultural mnemotechniques; in the same way intertextuality may be interpreted as a tool of active remembering. From the perspective of the semiotics of culture the above-mentioned canon-based hypertexts serve not only as memory-devices but as examples of cultural autocommunication as well. While religion as one of the most crucial „cultural systems” (Geertz) influences a lot of other subsystems of the semiosphere (Lotman), intertextual relations to the canon of religious texts vitalize the hypotext and create the whole set of new meanings, strengthening semiosis and dynamizing culture at the same time.